2009
DOI: 10.1097/mph.0b013e3181a6dea4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma in Turkish Children

Abstract: The survival rates in children with local disease are comparable with the results of developed countries; however, the results in children with advanced disease are still not satisfactory. To improve the outcome, especially in children with advanced disease, more effective chemotherapy regimens and molecular therapies should be investigated. Sharing the knowledge and capacity building to improve the treatment results in NBL are also critical for developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
2
8
1
1
Order By: Relevance
“…Compared with the current study, the reported studies, showed higher incidence of infants (45%) [13] and lower male to female ratio (1.3: 1) [14] and this may be explained by higher total number of patients (n = 500 - 594) in their studies.…”
Section: Discussioncontrasting
confidence: 84%
“…Compared with the current study, the reported studies, showed higher incidence of infants (45%) [13] and lower male to female ratio (1.3: 1) [14] and this may be explained by higher total number of patients (n = 500 - 594) in their studies.…”
Section: Discussioncontrasting
confidence: 84%
“…1 This potentially introduces batch effects and other variations that are largely unpredictable, including adoption of new microarray chip designs based on manufacturer design improvements. 17, 18, 19 We conduct CV for each model on the training set, followed by EV on the validation set.…”
Section: Methodsmentioning
confidence: 99%
“…Although retrospective analysis of neuroblastoma statistics indicates an overall improvement of treatment success, mortality rates for advanced-stage neuroblastoma are still high. 18, 19 The International Neuroblastoma Risk Group has established a set of clinical factors for predicting disease recurrence and survival. These clinical factors include disease stage, age of the patient at diagnosis, histological features and several genetic markers.…”
Section: Introductionmentioning
confidence: 99%
“…In our series, 95% of the PNTs occurred in children under five years of age, and of those, half occurred in children less than one year old. Based on the literature (18,19), girls are more likely to suffer from PNTs than boys are; however, in our research, there were slightly more boys than girls with PNTs (1.15: 1).…”
Section: Discussionmentioning
confidence: 46%